L’emploi du temps : travail et désoeuvrement dans Countenance de Fiona Tan - Bonin, Vincent (Ciel variable)

(untitled) (Les Productions Ciel variable, 2005)
Abstract In the installation Countenance (2001), Fiona Tan uses film to quote the archiving and photographing methods behind August Sander's photographic recension project Menschen des 20. Jahrhunderts (Men of the twentieth century). Like Sander, Tan compiles an impressive sample of portraits corresponding to various rubrics in a typology of professions and trades performed by Germans.Along with the recording of time passing, the change from one medium to another neutralizes any attempt to identify the typology as predominant over the phenomeno-logical experience of the image. At loose ends in front of the camera, the subjects are freed, even if momentarily, of the need to be socially accepted through their work. Although it does not erase singularities, this inactivity also constitutes a measurement of commonality between individuals.